Identifying and examining motivational profiles : distinct typologies with blended motives - Thomson, Margareta Maria (SAGE Research Methods. Cases., 2018)
This case study describes a dissertation research project in which a mixed-methods sequential explanatory design was used. Both quantitative (survey) and qualitative (interviews) data were collected to identify and examine typologies of preservice teachers (N = 215) with different motivational profiles. Furthermore, the study explored differences among the identified typologies regarding participants' demographics and teaching beliefs. The research process, study design, findings, and lessons learned are described in this case study.